Índios Imperiais: os botocudos, os militares e a colonização do Rio Doce (Espírito Santo, 1824-1845) - Marinato, Francieli Aparecida (2007)
This research analyses the process of colonization in espírito-santense part of the rio Doce, started in 1800, and the politics conducted to the native populations of this territory, usually called Botocudos. It is placed especially in the period that begins in 1824, when the new Imperial Government determined the instalation of the Diretoria de Índios do Rio Doce to group the Botocudos in retirings, until 1845, when the new legislation changed the brazilian indigenous politics. It stands out the performance of the militaries and of the quarters to the territorial conquest and like a support of the colonization of the region and the persistent resistance of the Botocudos in respect to these enclaves. It demonstrates the offensive war among indigenous, settlers and militaries, as well as the strategies of negotiation of interests and the organization of ways of survival and adaptation into the colonial situation by the indigenous populations. Using the correspondences of the directors of the indigenous with the Provincial and Imperial Governments, it analyses the discuss of pacification in the brazilian First Reign; the financial crisis to the whole implantation of the project of indigenous colonization and integration; the forms of contact and attraction of the Botocudos, their reactions and the kinship developed with the Diretoria in his constant traffic among forest and retirings; and the ways of adaptation and companionship of the retired and recruited indigenous to the compulsory work in its subaltern condition next to the scarce society that appeared in the borders of rio Doce. The results emphasize the breakdown of the projects of indigenous colonization and pacification because the resistance of the Botocudos and the limitations and inefficiency of the colonial limits, over all because the resourceless and logistical means. They also demonstrate that, in spite of failing of the colonial undertaking, arose in the Doce a new society with fights for posts, lands and social position, where men of property and militaries gained prominence. This society was marked by a strong indigenous presence, who did not maintain subaltern, but showed and negotiated its interests and undertook a resistance with many faces against the colonial project.